Treatment of Inherited Platelet Disorders: Current Status and Future Options - Bargehr, Caroline; Knöfler, Ralf; Streif, Werner (Hämostaseologie, 2023)
Inherited platelet disorders (IPDs) comprise a heterogeneous group of entities that manifest with variable bleeding tendencies. For successful treatment, the underlying platelet disorder, bleeding severity and location, age, and sex must be considered in the broader clinical context. Previous information from the AWMF S2K guideline #086–004 (www.awmf.org) is evaluated for validity and supplemented by information of new available and future treatment options and clinical scenarios that need specific measures. Special attention is given to the treatment of menorrhagia and risk management during pregnancy in women with IPDs. Established treatment options of IPDs include local hemostatic treatment, tranexamic acid, desmopressin, platelet concentrates, and recombinant activated factor VII. Hematopoietic stem cell therapy is a curative approach for selected patients. We also provide an outlook on promising new therapies. These include autologous hematopoietic stem cell gene therapy, artificial platelets and nanoparticles, and various other procoagulant treatments that are currently tested in clinical trials in the context of hemophilia.
Keywords: blood platelet disorder; therapy; inherited platelet disorder